Pengaruh Viral Marketing Dan Online Customer Review Terhadap Keputusan Pembelian Produk Kosmetik Lipstik Hanasui Di Platfrom Tiktok Shop - Nabila Oktaviani; Yulianto (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Social media has become a significant factor in shaping consumer behavior, particularly regardingpurchasing decisions. This study aims to assess the impact of Viral Marketing and Online CustomerReviews on the purchasing decisions for Hanasui lipstick products available in the TikTok shop, bothindividually and collectively. This study employs a quantitative descriptive method, utilizing onlinequestionnaires distributed to 130 respondents who have purchased Hanasui lipstick products throughthe TikTok Shop. Data analysis was conducted using SPSS version 25. This included instrument testing(validity and reliability testing), classical assumption testing (normality, multicollinearity, andheteroscedasticity tests), multiple linear regression analysis, and hypothesis testing (t-tests, F-tests, andthe coefficient of determination). The study's results show that Viral Marketing (X1) significantlyinfluences Purchasing Decisions (Y), with a significance value of 0.000 < 0.05 and a calculated t-valueof 7.268, which is greater than the t-table value of 1.978. The impact of Online Customer Reviews (X2)on Purchasing Decisions is both positive and significant. The significance value is 0.008, which is lessthan 0.05, and the calculated t- value is 2.680, surpassing the t-table value of 1.978. Additionally, whenconsidering both variables together, there is a significant effect on Purchasing Decisions. This issupported by a calculated F-value of 146.871, which is greater than the F-table value of 3.067, alongwith a significance level of 0.000, also below 0.05. The Adjusted R Square value of 0.693 shows that69.3% of purchasing decisions are influenced by viral marketing and online customer reviews, while theremaining 30.7% are affected by other factors beyond this study.Keywords: Trader Satisfaction, Market Management, Traditional Market, Service Quality,Qualitative Research